Creative SEL: Using Hands-On Projects to Boost Social-Emotional Learning - Michele Haiken, Michele Haiken, Mark Gura (ASCD, 2023)
This collection of creative lessons offers ideas for integrating design thinking, literacy and STEAM to drive SEL skills including self-awareness, self-management, mindfulness, responsible decision-making and social awareness. Research shows that creativity can be beneficial for mental health and can help build critical skills such as empathy and introspection, while social-emotional learning (SEL) is an integral part of education and human development. This book bridges these two ideas with a series of creative projects that foster SEL learning by promoting growth mindset, supporting mindfulness, offering ways to cope with anxiety and stress, and encouraging and guiding positive social activism. Opening with an overview of research behind the integration of SEL and creativity, the book then features a variety of lessons based on the above themes, illustrating how to deepen SEL by integrating the arts and STEAM learning in creative and authentic ways. The activities are drawn from the work of the authors and a diverse group of educator contributors to provide engaging, insightful and culturally responsive learning opportunities appropriate for traditional or online/blended learning environments. The book: * Highlights a diverse array of educators, innovators and design-thinkers who share their insights on SEL, STEAM and creativity. * Offers an accessible and fun approach to teaching SEL, which is critical to education and human development. * Guides teachers in implementing the following ISTE Standards for Students: Creative Communicator, Innovative Designer and Knowledge Constructor. This book invites teachers to consider a variety of formats - print and digital, audio, video games and more - and shows how helping students become creators and design-thinkers can foster SEL. Audience: K-12 educators